Integrated nursing of Traditional Chinese and Western medicine for a patient undergoing femoro-popliteal artificial vessel bypass surgery (股-腘动脉人工血管转流术1例围手术期中西医结合护理体会) - WANG Meiyu (王美玉); NIU Shaohui (牛少辉); ZHI Hui (智慧) (Journal of International Translational Medicine Limited, 2022)
The femoro-popliteal artificial vessel bypass surgery is an effective operation for the treatment of aeriosclerosis obliterations, and related perioperative nursing is critical to the patient. This paper summerzied the perioperative nursing experience in a patient undergoing femoro-popliteal artificial vessel bypass surgery for aeriosclerosis obliterations. Key issues of perioperative nuring included psychological intervention, illness observation, prevention of postoperative complications, dietary guidance, rehabilitation exercise, pain control. The goal of appling Integrated Traditional Chinese and Western medicine nursing is to relieve neagaive emotions of the patient, improve the treatment compliance and prevent the postoperative complications. (股-腘动脉人工自体血管转流术是治疗动脉硬化性闭塞症(ASO)的有效术式, 其围手术期的护理至关重要。本文总结1例股-腘动脉人工自体血管转流术合并抑郁症患者的围手术期护理经验, 包括心理干预、病情观察、并发症预防、饮食指导、康复锻炼、疼痛干预等。通过采用中西医结合的护理方法, 进而起到改善患者负性情绪、提高治疗依从性和预防并发症的积极作用。)